Impact of graft‐versus‐lymphoma effect on outcomes after reduced intensity conditioned‐alemtuzumab allogeneic haematopoietic stem cell transplantation for patients with mature lymphoid malignancies. (22nd November 2018) - Brierley, Charlotte K.; Jones, Francesca M.; Hanlon, Katharine; Peniket, Andy J.; Hatton, Chris; Collins, Graham P.; Schuh, Anna; Medd, Patrick; Clark, Andrew; Ward, Janice; Chaganti, Sridar; Malladi, Ram; et al.
Summary: Allogeneic haematopoietic stem cell transplant (allo‐HSCT) offers potentially curative therapy for patients with relapsed/refractory lymphoid malignancies. Reduced‐intensity conditioning (RIC) with Alemtuzumab reduces transplant‐related mortality and graft‐versus‐host disease (GvHD), but may be associated with increased risk of relapse. With the aim of studying the effect of GVHD and donor lymphocyte infusions (DLI) on relapse, we performed a retrospective study of 288 patients (57% non‐Hodgkin lymphoma, 24% Hodgkin lymphoma and 19% chronic lymphocytic leukaemia; 58% were relapsed/refractory) who underwent RIC‐Alemtuzumab‐HSCT between 2000 and 2012. Median follow‐up time for survivors was 64 months. Five‐year overall survival, relapse incidence, GvHD/relapse‐free survival and non‐relapse mortality were 47%, 33%, 37% and 28% respectively. Cumulative incidence of grade II‐IV acute and extensive chronic GvHD was 22% and 21% at 100 days and 5 years respectively. On multivariate analysis, presence of GvHD ( P = 0·03) and unrelated donor type ( P = 0·03) were protective of relapse. 62/288 patients received DLI for either mixed donor chimerism (prophylactic DLI, n = 37) or clinical relapse (therapeutic DLI, n = 25). Prophylactic and therapeutic DLI successfully converted the patient to full or stable mixed donor chimerism in 78% and 56% of patients respectively. These data demonstrate good long‐term outcomes and support the concept of the graft‐vs‐lymphoma effect as a key protective factor against relapse following RIC‐Alemtuzumab allo‐HSCT for patients with mature lymphoid malignancies.